Myocarditis and the military patient. Issue 3 (5th August 2015) - Cox, Andrew T; White, S; Ayalew, Y; Boos, C; Haworth, K; McKenna, WJ
Abstract : Myocarditis, simply defined as inflammation of the heart muscle, is a commonly encountered cardiac disease in primary and secondary care, both in the UK and on Operational deployments. In the UK Armed Forces, myocarditis results in deaths as well as the premature termination of military careers on medical grounds. The aetiology is usually the result of a number of infectious aetiologies with viruses being the most common pathogens in the vast majority of cases. However, it may also be the result of autoimmune activation, chemical or pharmacological toxins, environmental insult or hypersensitivity reactions. Particular aetiologies that are more likely to be seen in a military population are discussed and include certain infections, smallpox vaccine, and hyperthermia and hypothermia. The clinical features can be highly variable ranging from an asymptomatic infection to fulminant heart failure. Features pertinent to the military doctor, including the natural history, investigative modalities and management strategies, with a particular emphasis on the occupational impact of myocarditis in the UK Armed Forces are reviewed.